Potential carbon sequestration and nitrogen cycling in long-term organic management systems. Issue 6 (12th January 2017) - Bhowmik, Arnab; Fortuna, Ann-Marie; Cihacek, Larry J.; Bary, Andy I.; Carr, Patrick M.; Cogger, Craig G.
Abstract: The fertility and soil health of organic agroecosystems are determined in part by the size and turnover rate of soil carbon (C) and nitrogen (N) pools. Our research contrasts the effects of best management practices (BMP) (reduction in soil disturbance, addition of organic amendments) on C and N cycling in soils from two field sites representing five organic agroecosystems. Total soil organic C (SOC), a standard measure of soil health, contains equal amounts of biologically and non-biologically active C that is not associated with release of mineral N. A three-pool first-order model can be used to estimate the size and turnover rates of C pools but requires data from a long-term incubation. Our research highlights the use of two rapid C fractions, hydrolysable and permanganate (0.02 M) oxidizable C, to assess shifts in biologically active C. Adoption of BMP in organic management systems reduced the partitioning of C to the active pool while augmenting the slow pool C. These pools are associated with potentially mineralizable N supplied by residues, amendments and soil organic matter affecting the concentration and release of mineral N to crops. Our data show that minimizing disturbance (no tillage, pasture) and mixed compost additions have the potential to reduce carbon dioxide emissions while enhancing slow pool C and or its turnover, a reservoir of nutrients available to the soil biota. Use of these rapid, sensitive indicators of biological C activity will aid growers in determining whether a BMP fosters nutrient loss or retention prior to shifts in total SOC.